Experimental validation of quadratic-boost-zeta converter based on coat circuit - Ali, Ahmed Mahmood; Hassan, Turki Kahawish (Institute of Advanced Engineering and Science, 2023)
This work proposed a high step-up DC-DC converter with a voltage gain of 12 at a duty cycle of 48.25% with a single active switch. The new design combines the quadratic-boost converter and an isolated zeta converter with a single-stage coat circuit by a transformer with a trans ratio of 2.3. This can result in low voltage stress on switch and diodes with low conduction losses without using an additional clamp circuit, which in turn causes an increase in total efficiency. It has continuous and low ripples in the input and output currents. The voltage conversion ratio and the component voltage stresses are calculated in continuous conduction mode (CCM). The prototype was constructed and tested practically while considering an input voltage of 30 V, an input power of 240 W, an output voltage of 360 V, and a switching frequency of 100 kHz to validate the theoretical evaluations. The maximum efficiency at maximum output power is 94.5%.